Student compliance with indications for intravenous cannulation during clinical learning - C Vincent-Lambert; B van Nugteren (South African Medical Association, 2015)
Background. Intravenous (IV) cannulation is a commonly performed procedure that is taught to a number of health science students. As with most invasive medical interventions, there is a possibility of unintended adverse effects. Therefore, IV cannulation should only be performed for a clearly established need. Objective. To assess the extent to which emergency medical care students, during the course of their clinical learning, establish IV access in patients without a clearly documented indication. Methods. A retrospective analysis of historical data from a clinical learning database was done to investigate whether patients seen by students over a 2-year period received IV cannulation in line with indications taught to students. Results. Of the 5 893 cases reviewed, 1 862 (32%) were cannulated intravenously. Of these, 426 (23%) did not have a clearly documented indication that had been taught for the procedure. Therefore, these patients may potentially have been ‘overtreated’. Conclusion. This study demonstrates that a high number of IV lines were established by students, with no clearly documented indication. This potential overtreatment may in part be attributed to pressures placed on students to achieve the minimum prescribed number of skills. Such practices remain common in medical education and may be detrimental to the patient. Medical educators need to ensure that students value the patient rather than the procedure. Further research needs to be conducted to investigate and identify other possible reasons for overtreatment of patients by medical students.